Prevalence of dural puncture headache after caesarean section at a tertiary hospital in the Gambia - Matthew Anyanwu; Admire Coker; Simon Donkor (PLoS ONE, 2025)
Background Following a caesarean section performed under spinal anaesthesia, a common complication is post-dural puncture headache (PDPH). Spinal anaesthesia has become the most common anaesthetic procedure during caesarean section in our practice. Therefore, knowing the prevalence and risk factors of PDPH will inform practice and add value in our obstetrics practice. Methodology A cross-sectional study was conducted at Edward Francis Small Teaching Hospital Banjul and data was effectively collected from August to October 2023. A structured data collection tool was used. The data was entered into a computer database and analyzed using the SPSS version 26. Pain was graded using a 10-cm visual analogue scale. Results were expressed in simple descriptive statistics and test of significance was set at p-value 0.05. Results A total of 89 participants with mean age of 28 years (SD ± 6.1) and majority 45(50.6%), between 21 to 30 years. Majority had low parity (0 to 3), 64(71.9%), emergency CS of 71(79.8%), while only 20.2% (n = 18) were elective CS. Overall prevalence of Post Dural Puncture Headache (PDPH) was 42.7% with majority of cases presenting with Occipital headache (71%), lasting for 3hrs (42%). A statistically significant association between PDPH and Gestational age with p-value (p = 0.02); number of attempts with p-value (p = 0.01); larger needle gauge and number of CSF drops (p = 0.01), respectively were observed. Conclusion Prevalence of PDPH was high and associated with the use of large needle gauges, multiple attempts and increased CSF drops. Patients that underwent emergency CS, have a higher risk of developing Post-Dural Puncture Headache.